Monocyte to High-Density Lipoprotein Ratio (MHR) as A Predictor of Major Cardiovascular Events in Acute Myocardial Infarction Patients with ST-Segment Elevation in Patients Undergoing Primary Percutaneous Coronary Intervention at Haji Adam Malik Central General Hospital - Nikensari, Grace; Nasution, Ali Nafiah; Siregar, Abdullah Afif (CoinReads Media Prima, 2024)
Introduction: IMA-EST is a cardiovascular disease with high mortality and morbidity. Therefore, tools (markers) to efficiently predict mortality rates are essential to reduce these rates for effective management. Since most of the available literature suggests that MHR value can be used as a predictor of MACE, we are interested in examining MHR as a predictor of MACE in IMA-EST patients undergoing primary PCIMethods: This type of study was an observational analytic study with the research design used is an ambispective cohort. namely assessing the role of MHR Ratio as a predictor of prognosis after primary MACE in IMAEST patients. This study was conducted at HAM Hospital Medan from April-June 2023. Patients who met the inclusion and exclusion criteria were assessed for laboratory parameters such as triglyceride levels and calculated MHR index, then MACE was observed in patients who underwent primary IKP. The MACE assessed was cardiovascular death, malignant arrhythmia, cardiogenic shock, and acute heart failure during hospitalisation and 30 days post-treatment either through control at the polyclinic or by telephone and interview. Results: A total of 55 samples were obtained. The GRACE Score and MHR parameters have an area under the ROC curve > 0.7. The MHR parameter had a sensitivity of 69.2% and specificity of 64.3% and a p value <0.05. Based on ROC curve analysis, the cut-off-point parameter for estimating predictors of MVC was 22.48. The GRACE Score coefficient is 0.466 with a significance value (p value) of 0.001 that there is a correlation between the GRACE Score parameters and MHR parameters. Conclusion: High monocyte counts have an association of low HDL-C levels in the development of atherosclerosis and MACE.